2015
DOI: 10.1590/1516-4446-2014-1620
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of bipolar disorder: characterization and strategies for early intervention

Abstract: Objective: To characterize the early stages of bipolar disorder (BD), defined as the clinical prodrome/ subsyndromal stage and first-episode phase, and strategies for their respective treatment. Methods: A selective literature search of the PubMed, Embase, PsycINFO, and ISI databases from inception until March 2014 was performed. Included in this review were articles that a) characterized prodromal and first-episode stages of BD or b) detailed efficacy and safety/tolerability of interventions in patients consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…28,29 Several studies have recognized mood lability, major depressive episodes, subsyndromal manic symptoms, a diagnosis of a bipolar spectrum disorder (such as cyclothymia or BD not otherwise specified), and mood-congruent psychotic symptoms as precursors of BD. [30][31][32] On the other hand, in clinical practice, identification of a symptomatic high-risk BD phase is complicated by the complex nature of dimensions of this disorder, by potentially different symptom presentations in children and adolescents, 5,21,33 and by the blurred lines between the prodrome and the disease itself. 34 Retrospective and prospective studies have revealed a pattern of putative prodromal symptoms, of which mood lability/mood swings/cyclothymic features, depressive mood, racing thoughts, irritability, and physical agitation are most commonly reported.…”
Section: Clinical Presentation Of Early Stagesmentioning
confidence: 99%
“…28,29 Several studies have recognized mood lability, major depressive episodes, subsyndromal manic symptoms, a diagnosis of a bipolar spectrum disorder (such as cyclothymia or BD not otherwise specified), and mood-congruent psychotic symptoms as precursors of BD. [30][31][32] On the other hand, in clinical practice, identification of a symptomatic high-risk BD phase is complicated by the complex nature of dimensions of this disorder, by potentially different symptom presentations in children and adolescents, 5,21,33 and by the blurred lines between the prodrome and the disease itself. 34 Retrospective and prospective studies have revealed a pattern of putative prodromal symptoms, of which mood lability/mood swings/cyclothymic features, depressive mood, racing thoughts, irritability, and physical agitation are most commonly reported.…”
Section: Clinical Presentation Of Early Stagesmentioning
confidence: 99%
“…The mean age of onset for BD is between 20 and 30 years, and risk of onset decreases with age thereafter (1,2). The long interval between early symptoms, correct diagnosis, and adequate treatment (5.8-6.7 years) (5,6) is associated with a worsened clinical course and a substantial burden of illness (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Staging studies of bipolar disorder (BD) in offspring and selecting at‐risk samples provide significant insights into the neurobiology of the early stages of BD . The identification of clinical, cellular, and molecular underpinnings of preclinical stages has the potential to inform putatively preventive interventions, particularly those designed to delay, reduce the severity of, or even prevent the onset of full‐blown BD .…”
Section: Introductionmentioning
confidence: 99%